The substance basis of Poria ameliorates hypothyroidism other than hyperthyroidism based on proteomics and metabolomics. Issue 9 (15th July 2020) - Han, Xueying; Xiao, Hang; Chen, Jing; Xu, Weiqun; Dou, Deqiang
Abstract: Integrated metabolomics and proteomics analysis was carried out to study the effects of Poria and its split components (volatile oil, triterpenoid, oligosaccharide, amino acid, and crude polysaccharide) on rats of normal physiological model, hyperthyroidism model, and hypothyroidism model to explore the substance basis of Poria for hypothyroidism from the perspective of a holistic view in substance and energy metalism. The key pathways regulating substance and energy metabolism were screened, encompassing tricarboxylic acid cycle pathway, glycolysis/ gluconeogenesis pathways, biosynthesis of amino acid pathway, fatty acid biosynthesis pathway, pentose phosphate pathway, peroxisome proliferator‐activated receptors pathway, etc Poria and its split components showed promoting effects on substance and energy metabolism in normal model, while showed amelioration effects on hypothyroidism model at different degrees, and had no significant improvement effects on hyperthyroidism in rats. Volatile oil, triterpenoid, and crude polysaccharide from Poria were regarded as substance basis of Poria ameliorating hypothyroidism other than hyperthyroidism. This work also revealed the feasibility of metabolomics and proteomics analysis to elucidate the effective substance basis of traditional Chinese medicine from a new viewpoint based on its effects on substance and energy metabolism.